The early-stage comprehensive costs of routine PrEP implementation and scale-up in Zambia - Cheryl Hendrickson; Lawrence C. Long; Craig van Rensburg; Cassidy W. Claassen; Mwansa Njelesani; Crispin Moyo; Lloyd Mulenga; Heidi O'Bra; Colin A. Russell; Brooke E. Nichols (Public Library of Science (PLoS), 2022)
Pre-exposure prophylaxis (PrEP) is an effective HIV prevention option, but cost-effectiveness is sensitive to implementation and program costs. Studies indicate that, in addition to direct delivery cost, PrEP provision requires substantial demand creation and client support to encourage PrEP initiation and persistence. We estimated the cost of providing PrEP in Zambia through different PrEP delivery models. Taking a guidelines-based approach for visits, labs and drugs, we estimated the annual cost of providing PrEP per client for five delivery models: one focused on key populations (men-who-have-sex-with-men (MSM) and female sex workers (FSW), one on adolescent girls and young women (AGYW), and three integrated programs (operated within HIV counselling and testing services at primary healthcare centres). Program start-up and support costs were based on program expenditure data and number of PrEP sites and clients in 2018. PrEP clinic visit costs were based on micro-costing at two PrEP delivery sites (2018 USD). Costs are presented in 2018 prices and inflated to 2021 prices. The annual cost/PrEP client varied by service delivery model, from $394 (AGYW) to $655 (integrated model). Cost differences were driven largely by client volume, which impacted the relative costs of program support and technical assistance assigned to each PrEP client. Direct service delivery costs ranged narrowly from $205-212/PrEP-client and were a key component in the cost of PrEP, representing 35-65% of total costs. The results show that, even when integrated into full service delivery models, accessing vulnerable, marginalised populations at substantial risk of HIV infection is likely to cost more than previously estimated due to the programmatic costs involved in community sensitization and client support. Improved data on individual client resource usage and outcomes is required to get a better understanding of the true resource utilization, expected outcomes and annual costs of different PrEP service delivery programs in Zambia.